Studi Korelasi Uniaxial Compressive Strength Dan Rebound Number Schmidt Hammer Pada Batulanau Formasi Pulau Balang Dan Kampung Baru Daerah Kalimantan Timur - Sri Wahyuni; Tommy Trides; Harjuni Hasan; Revia Oktaviani; Shalaho Dina Devy (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Uniaxial Compressive Strength is a test method to classify the strength and characterization of intact rock. Where it is important information in determining the strength and characteristics of a rock obtained by testing using the UCS tool. In this research, an alternative is made in determining the UCS value precisely and easily, namely by using the schmidt hammer test and compressive strength test. Therefore, this research aims to obtain the correlation value between the results of the compressive strength test and the schmidt hammer test on siltstone.This research is a quantitative research, so that to obtain accurate calculation data, testing methods are used in the form of compressive strength tests on rocks and schmidt hammer tests, which in this case are tested on siltstone samples. In this study, 2 rock formations were used, including the Pulau Balang formation and the Kampung Baru formation, so that the accuracy of the test results can be obtained properly. Based on the results of observations and calculations that have been made, it can be concluded that the correlation of the uniaxial compressive strength value with the rebound number schmidt hammer value shows a positive linear correlation between the UCS value and the rebound number schmidt hammer value, in this case it can be seen when the uniaxial compressive strength value is higher, the rebound number schmidt hammer value is also higher.